Subordinate clause found in dracula novel by bram stoker - Putri, Luh De Mila Noviana; Maharani, Putu Devi; Putra, I Gusti Bagus Wahyu Nugraha (Institut Pariwisata dan Bisnis Internasional, 2020)
The purpose of this research is to find out the functions of subordinate clauses in Dracula novel by Bram Stoker. The data of this study were taken from Dracula novel by Bram Stoker. This study focused on analysing the subordinate clause in complex declarative sentences found in Dracula novel by Bram Stoker. The theory used in this research is the theory by Aarts (2001) about types of function of subordinate clause which consist of clause functioning as subject, clause functioning as direct object, clause functioning as adjunct and clause functioning as complement within phrase and supported with theory by Quirk and Sydney’s (1973) theory on their book entitled a University of Grammar. Then, to analyze the functions of subordinate clause the qualitative strategy is used. The result of the research shows that in Dracula novel by Bram Stoker found 194 data and has a complete subordinate clause function. They are clause functioning as subject, clause functioning as direct object, clause functioning as adjunct and clause function as complement within phrase.